The Many within the One: A Neurophilosophical Inquiry into Consciousness, Identity, and Dissociation - Belli, Hasan; Lacin, Selin (Journal of NeuroPhilosophy, 2025)
This paper explores the ontological and epistemological implications of consciousness through an interdisciplinary synthesis of analytic idealism, quantum panprotopsychism, and the clinical model of Dissociative Identity Disorder. Drawing on Bernardo Kastrup’s analytic idealism, it argues that reality is fundamentally mental, constituted by a universal field of consciousness whose apparent multiplicity emerges from self-differentiation rather than physical fragmentation. Quantum ontology, particularly the principles of wave–particle duality and entanglement, serves as a heuristic metaphor for this dynamic interplay between unity and plurality within consciousness. The study examines the parallels between quantum models of cognition and psychodynamic structures of the self, proposing that the coexistence of “wave-state” (holistic) and “particle-state” (localized) consciousness reflects the dual nature of human awareness. Clinically, Dissociative Identity Disorder provides an empirically grounded analogy for understanding how one conscious system can host multiple, semi-autonomous centers of experience while maintaining overarching functional unity. Neuroimaging and trauma-theory data are discussed as evidence of structural dissociation, which, when reinterpreted philosophically, mirrors the idealist view of differentiated consciousness within a unified ontological field. However, the paper emphasizes that such analogies remain metaphorical rather than mechanistic, preserving the scientific and ethical integrity of psychiatric phenomena. Ultimately, this synthesis proposes a conceptual bridge between metaphysics and clinical science, situating consciousness as both a neurobiological and cosmological principle. While speculative, the framework provides a philosophically coherent and phenomenologically informed model for re-examining the nature of mind, matter, and identity in a post-materialist paradigm.